Commerce, finance and statecraft: Histories of England, 1600-1780 - Ben Dew (Manchester University Press, 2018)
In the seventeenth and eighteenth centuries, historians of England pioneered a series of new approaches to the history of economic policy. Commerce, finance and statecraft charts the development of these forms of writing and explores the role they played in the period's economic, political and historiographical thought. Through doing so, the book makes a significant intervention in the study of historiography, and provides an original account of early-modern and Enlightenment history. A broad selection of historical writing is discussed, ranging from the work of Francis Bacon and William Camden in the Jacobean era, through a series of accounts shaped by the English Civil War and the party-political conflicts that followed it, to the eighteenth-century's major account of British history: David Hume's History of England. Particular attention is paid to the historiographical context in which historians worked and the various ways they copied, adapted and contested one another's narratives. Such an approach enables the study to demonstrate that historical writing was the site of a wide-ranging, politically charged debate concerning the relationship that existed - and should have existed - between government and commerce at various moments in England's past.
Keywords: 330; History; Europe; Great Britain; General; Business & Economics; Economic History